Świecka tożsamość polskich Żydów jako żydowska tożsamość alternatywna - Włodarczyk, Tamara (Instytut Kultury Europejskiej UAM w Gnieźnie oraz Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2013)
The article discusses the issue of Jewish secular identity. Drawing on the studies of Irena Hurwic-Nowakowska, Konstanty Gebert and Heleny Datner, as well as own research, the author demonstrates the specific identity of a number of Polish Jews, whose notion of Jewish identity is not founded on religion but rooted in the broadly understood Jewish heritage
SECULAR IDENTITY OF POLISH JEWS AS ALTERNATIVE JEWISH IDENTITY
Summary:The notion of secular Jewish identity may be associated with the category of “non-Jewish Jews” conceived by Isaac Deutscher. One of the subcategories comprises “Jews without Judaism”, and the denomination reflects the nature of the identity shift among Polish Jews. After World War 2, secular Jewish identity in Poland was shaped by the Holocaust, the primacy of materialist worldview, the social and political situation in the country as well as the weakness of Jewish religious organisations due the emigration of religious Jews. Drawing on the studies of Irena Hurwic-Nowakowska, Konstanty Gebert and Heleny Datner, as well as own research, the author attempts to answer the question whether secular identity may be recognised as fully-fledged Jewish identity. The statements from Jewish leaders representing various backgrounds (The Social-Cultural Jewish Society in Poland, Jewish religious communities and other organisations), present their views on their own identity and identification, as well as on collective identity and the changes it undergoes.
Keywords: POLISH JEWS; JEWISH IDENTITY; SECULAR IDENTITY